2022
DOI: 10.1007/s00330-022-09151-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of deep learning–based image reconstruction in MR imaging of the shoulder joint to improve image quality and reduce scan time

Abstract: Objectives To compare the image quality and diagnostic performance of conventional motion-corrected periodically rotated overlapping parallel line with enhanced reconstruction (PROPELLER) MRI sequences with post-processed PROPELLER MRI sequences using deep learning-based (DL) reconstructions. Methods In this prospective study of 30 patients, conventional (19 min 18 s) and accelerated MRI sequences (7 min 16 s) using the PROPELLER technique were acquired. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…High-eld imaging at 3 tesla (3 T) has been shown to outperform 1.5 T for articular joint imaging. In particular, TRUEFISP at 3 T offered excellent cartilage-joint uid contrast in previous investigations and that cartilage was also better visualized with TRUEFISP than SPACE sequences [9,28,29].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…High-eld imaging at 3 tesla (3 T) has been shown to outperform 1.5 T for articular joint imaging. In particular, TRUEFISP at 3 T offered excellent cartilage-joint uid contrast in previous investigations and that cartilage was also better visualized with TRUEFISP than SPACE sequences [9,28,29].…”
Section: Discussionsupporting
confidence: 49%
“…Meanwhile, 3D-GRE sequences showed moderate reproducibility for glenohumeral joint space measurement, while 2D sequences displaying varying reproducibility results. The reasonable answer to slight agreement for T 2 w FSE could be the motion artifacts due to the heavy breathing of volunteers or the pulsation of the adjacent vessels lead to lower image quality of this technique [9]. Furthermore, the later echoes in longer echo train length might also be associated with a decrease in the overall SNR, CNR, and more spatial blurring [7,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The image quality satisfaction survey among 400 patients received high scores in DL-MRI from all radiologists. Kaniewska et al [43] also declared that DLR could improve diagnostic accuracy and image quality with thorough assessment of the subacromial bursa and good agreement for other shoulder structures.…”
Section: Diagnosismentioning
confidence: 99%
“…In a previous study, DL-MRI sequences were found to be more effective than traditional MRI sequences in detecting SbA bursal thickening, although the extent of this thickening was not extensively explored ( 19 ). Assessing the degree of thickness in the intra-articular bursa can provide valuable insights into the severity of the patient’s condition, as it often correlates with the level of shoulder pain experienced.…”
Section: Introductionmentioning
confidence: 99%